Faktor Resiko Terhadap Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Pulau Pinang Kabupaten Lahat Tahun 2022: Risk Factors for the Occurrence of Diarrhea in Toddlers in the Working Area of ​​Pulau Pinang Community Health Center, Lahat Regency in 2022 - Hartati, Sri; Kamesyworo; Elviani, Yeni (Chakra Brahmanda Lentera Institute, 2023)
Diarrheal disease is a major problem in developing countries, including Indonesia. Apart from being a cause of death, diarrhea is also a major cause of malnutrition which can cause death and can cause extraordinary events. Many factors directly or indirectly cause diarrhea. This study aims to determine the factors associated with the incidence of diarrhea in toddlers in the working area of the Pulau Pinang Public Health Center, Lahat Regency. This research uses analytic observation with cross sectional design with chi square test. Where this research analysis was carried out by identifying univariate and bivariate analysis, the instrument used was a questionnaire and was carried out directly with the respondents. The sample in this study were toddlers who were treated at the Pulau Pinang Health Center in Lahat Regency. The sampling technique used was purposive sampling with a total of 50 respondents and had inclusion criteria. The results of data analysis found that there was a relationship between exclusive breastfeeding and the incidence of diarrhea in children under five with a P value of 0.027, there was a relationship between nutritional status and the incidence of diarrhea in children under five with a P value of 0.019 and there was a relationship between mother's knowledge and the incidence of diarrhea in children under five with P-value 0.046. It is hoped that the Puskesmas health service can increase mothers' knowledge about the concept of diarrhea in toddlers through the socialization of health education in the working area of the Puskesmas.